Technological change and transition: relative contributions to worldwide growth during the 1990s - Oleg Badunenko; Daniel J. Henderson; Valentin Zelenyuk (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In this paper we used the procedures developed in the Kumar and Russell (2002) growth-accounting study to examine cross-country growth during the 1990's. Using a data set comprising developed, newly industrialized, developing and transitional economies, we decomposed the growth of output per worker into components attributable to technological catch-up, technological change and capital accumulation. In contrast to the study by Kumar and Russell (2002), which concluded that capital deepening was the major force of growth and change in the world income per worker distribution over the 1965-1990 period, our analysis showed that, during the 1990's, the major force in the further divergence of the rich and the poor was due to technological change, whereas capital accumulation played a lesser and opposite role. In further contrast, we found that efficiency changes (insignificantly) led (on average) to regress rather than progress. Finally, although on average we found that transitional economies performed similar to the rest of the world, the procedure was able to discover some interesting patterns within the set of transitional countries.
Keywords: O47; P27; P52; 330; Data Envelopment Analysis; Growth; Convergence; Transitional Economies; Wirtschaftswachstum; Data-Envelopment-Analyse; Entwicklungskonvergenz; Technischer Fortschritt; Investition; Übergangswirtschaft; Aufstrebende Märkte; Welt; Schwellenländer; Transformationsstaaten